Machine learning and principles and practice of knowledge discovery in databases: International Workshops of ECML PKDD 2021, Virtual Event, September 13-17, 2021, proceedings, part I - Kamp, Michael; Koprinska, Irena; Bibal, Adrien; Bouadi, Tassadit; Frénay, Benoît; Galárraga, Luis; Oramas, José.; Adilova, Linara; Krishnamurthy, Yamuna; Kang, Bo; Largeron, Christine; Lijffijt, Jefrey; et al. (Communications in Computer and Information Science, 2021)
Advances in Interpretable Machine Learning and Artificial Intelligence -- Parallel, Distributed, and Federated Learning -- Graph Embedding and Mining -- Machine Learning for Irregular Time Series -- IoT, Edge, and Mobile for Embedded Machine Learning -- eXplainable Knowledge Discovery in Data Mining -- Bias and Fairness in AI -- International Workshop on Active Inference. .